Genome-Wide Transcriptional Regulation and Chromosome Structural Arrangement by GalR in E. coli - Qian, Zhong; Trostel, Andrei; Lewis, Dale E. A.; Lee, Sang Jun; He, Ximiao; Stringer, Anne M.; Wade, Joseph T.; Schneider, Thomas D.; Durfee, Tim; Adhya, Sankar (Frontiers in Molecular Biosciences, 2016)
The regulatory protein, GalR, is known for controlling transcription of genes related to D-galactose metabolism in Escherichia coli. Here, using a combination of experimental and bioinformatic approaches, we identify novel GalR binding sites upstream of several genes whose function is not directly related to D-galactose metabolism. Moreover, we do not observe regulation of these genes by GalR under standard growth conditions. Thus, our data indicate a broader regulatory role for GalR, and suggest that regulation by GalR is modulated by other factors. Surprisingly, we detect regulation of 158 transcripts by GalR, with few regulated genes being associated with a nearby GalR binding site. Based on our earlier observation of long-range interactions between distally bound GalR dimers, we propose that GalR indirectly regulates the transcription of many genes by inducing large-scale restructuring of the chromosome.